Pathogen inactivation of Dengue virus in red blood cells using amustaline and glutathione. Issue 12 (16th September 2017) - Aubry, Maite; Laughhunn, Andrew; Santa Maria, Felicia; Lanteri, Marion C.; Stassinopoulos, Adonis; Musso, Didier
Abstract : BACKGROUND: Dengue virus (DENV) is an arbovirus primarily transmitted through mosquito bite; however, DENV transfusion‐transmitted infections (TTIs) have been reported and asymptomatic DENV RNA–positive blood donors have been identified in endemic countries. DENV is considered a high‐risk pathogen for blood safety. One of the mitigation strategies to prevent arbovirus TTIs is pathogen inactivation. In this study we demonstrate that the amustaline and glutathione (S‐303/GSH) treatment previously found effective against Zika virus in red blood cells (RBCs) is also effective in inactivating DENV. STUDY DESIGN AND METHODS: Red blood cells were spiked with high levels of DENV. Viral RNA loads and infectious titers were measured in the untreated control and before and after pathogen inactivation treatment of RBC samples. DENV infectivity was also assessed over five successive cell culture passages to detect any potential residual replicative virus. RESULTS: The mean ± SD DENV titer in RBCs before inactivation was 6.61 ± 0.19 log 50% tissue culture infectious dose (TCID50 )/mL and the mean viral RNA load was 8.42 log genome equivalents/mL. No replicative DENV was detected either immediately after completion of treatment using S‐303/GSH or after cell culture passages. CONCLUSION: Treatment using S‐303/GSH inactivated high levels of DENV in RBCs to the limit of detection. In combination with previous studies showing the effective inactivation of DENV in plasma and platelets using the licensed amotosalen/UVA system, this study demonstrates that high levels of DENV can be inactivated in all blood components.